2014
DOI: 10.1093/carcin/bgu035
|View full text |Cite
|
Sign up to set email alerts
|

Tumor promoter-induced sulfiredoxin is required for mouse skin tumorigenesis

Abstract: Sulfiredoxin (Srx), the exclusive enzyme that reduces the hyperoxidized inactive form of peroxiredoxins (Prxs), has been found highly expressed in several types of human skin cancer. To determine whether Srx contributed to skin tumorigenesis in vivo, Srx null mice were generated on an FVB background. Mouse skin tumorigenesis was induced by a 7,12-dimethylbenz[α]anthracene/12-O-tetradecanoylphorbol-13-acetate (DMBA/TPA) protocol. We found that the number, volume and size of papillomas in Srx(-/-) mice were sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…Another study from Wei et al demonstrated high SRXN1 protein expression in human colon carcinoma and showed that Srxn1 knockout animals were resistant to carcinogenic induction [76]. In addition, SRXN1 expression is increased in different human skin malignancies [77,78] and gastric cancer [79].…”
Section: Discussionmentioning
confidence: 99%
“…Another study from Wei et al demonstrated high SRXN1 protein expression in human colon carcinoma and showed that Srxn1 knockout animals were resistant to carcinogenic induction [76]. In addition, SRXN1 expression is increased in different human skin malignancies [77,78] and gastric cancer [79].…”
Section: Discussionmentioning
confidence: 99%
“…The initial correlation of Srx to cancer emerged from its differential expression in the transformation-sensitive mouse JB6 epidermal cells [36]. It was further demonstrated that Srx is overexpressed in cancers of skin, lung, and rectum, but not in normal tissues, and has an oncogenic role in promoter-induced tumorigenesis of skin and colon, and in lung cancer cells [24][25][26]37,38], indicating that Srx might be targeted for cancer prevention or treatment. Here, we showed that the inhibition of Srx activity in human lung adenocarcinoma A549 cells causes oxidative stress, which in turn leads to mitochondrial damage resulting in apoptotic cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Srx protein is also over-expressed in renal cell carcinoma where it is proposed to be a good antibody target that can result in tumor cell death [74]. Srx expression is stimulated by TPA via MAPK/JNK ( c-Jun N-terminal kinase ) pathway in skin carcinogenesis and Srx depletion at least partially protects mice against DMBA( 7,12-dimethylbenz[a]anthracene )/TPA-induced skin carcinogenesis [75]. Srx is also necessary for colon carcinogenesis as it is highly over-expressed in colon tumor tissue compared to normal human colon, and Srx null mice are highly resistant to azoxymethane/dextran sulfate sodium -induced colon carcinogenesis [33].…”
Section: The Srx-prx Axis In Tumorigenesis and Cancer Progressionmentioning
confidence: 99%